SELF-ADAPTIVE MODEL BASED ON GOAL-ORIENTED REQUIREMENTS ENGINEERING FOR HANDLING SERVICE VARIABILITY (Journal of Information and Communication Technology, 2020)
Service system is currently facing environmental complexity problems, such as the need of a distributed, heterogeneous, decentralized, and interdependent system which operatesdynamically and unpredictably. This condition requires the service system to have an ability to adapt in order to realize sustainable functions. The success of service adaptation is determined by its ability to handle variability at runtime. The purpose of this research is to realize service flexibility through variability modeling, which is an extension of previous work to enrich the adaptability view. The methodology was developed through the monitor-analyse-plan-execute-knowledge control loops approach integrated into the adaptive service (service level) element within the adaptive enterprise service system metamodel based on goal-oriented requirements engineering. Service adaptation scenario was prepared through proactive and reactive adaptation mechanisms. For evaluation, the model was applied to the case of a configuration management system. The experimental results showed that the model is able to adapt to runtime variability and accomodates the growth of the service component items shown by the description of the system scalability. The proposed model has a better alternative design in analyzing variability with a total response that can be applicable in normal operations and overload. It also meets the expected level (level-5: adapting) of the adaptive capability maturity model as a standard for assessment of a service system adaptation.